The mediators of systemic inflammation in lipopolysaccharide-induced neonatal sepsis rat model - Ilhan, N.; Gul, H. F.; Susam, S.; Ilhan, N. (Wiley-Blackwell, 2016)
[Abstract Not Available]
41st FEBS Congress on Molecular and Systems Biology for a Better Life -- SEP 03-08, 2016 -- Kusadasi, TURKEY